Exploring Transformations in The Economic Structure of Family Farms in Poland from 2010–2020 - Bożena KARWAT-WOŹNIAK; Aleksandra PAWŁOWSKA; Paweł CHMIELIŃSKI (Communications of International Proceedings, 2025)
The aim of the study is to examine the dynamics of structural changes in Polish agriculture between 2010 and 2020, focusing on the process of land concentration in economically viable farms. The motivation stems from the growing convergence of family and industrial farming models and the implications for competitiveness and sustainability. The analysis is based on data from the Central Statistical Office, interpreted in the context of relevant literature. The findings indicate a significant decline in the number of farms, an increase in economic size, and a gradual improvement in competitiveness, although small farms still dominate the structure.
Keywords: farm structure; standard output; agrarian structure; Poland; 2010-2020